2022
DOI: 10.3390/pharmaceutics14102234
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polyethyleneimine (PEI)–Gold Nanocomposites Modulate Macrophage Activation and Reprogram Mouse Breast Triple-Negative MET-1 Tumor Immunological Microenvironment

Abstract: Nanomedicines based on inorganic nanoparticles have grown in the last decades due to the nanosystems’ versatility in the coating, tuneability, and physical and chemical properties. Nonetheless, concerns have been raised regarding the immunotropic profile of nanoparticles and how metallic nanoparticles affect the immune system. Cationic polymer nanoparticles are widely used for cell transfection and proved to exert an adjuvant immunomodulatory effect that improves the efficiency of conventional vaccines against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…For example, Mulens-Arias et al showed that polyethylenimine−gold nanocomplexes reversed the immune tumor microenvironment toward an M2 phenotype with immunosuppressive features by secreting TNF-α and CCL5. 81 Meanwhile, Cheng et al demonstrated how macrophages from both human and mouse were changed from a tumorigenic M2 to an M1-like phenotype adopting cGAMP nanoparticles, a form of IFN type I agonist. 70 Through the induction of ICD, nanoparticles also concurrently alter the polarity of TAM.…”
Section: Regulation Of Immune-related Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Mulens-Arias et al showed that polyethylenimine−gold nanocomplexes reversed the immune tumor microenvironment toward an M2 phenotype with immunosuppressive features by secreting TNF-α and CCL5. 81 Meanwhile, Cheng et al demonstrated how macrophages from both human and mouse were changed from a tumorigenic M2 to an M1-like phenotype adopting cGAMP nanoparticles, a form of IFN type I agonist. 70 Through the induction of ICD, nanoparticles also concurrently alter the polarity of TAM.…”
Section: Regulation Of Immune-related Cellsmentioning
confidence: 99%
“…110 Given the ability of PEI allowing the Au 3+ reduction to Au 0 and further nucleation into gold nanoparticles, Mulens-Arias et al designed cationic polyethylenimine (PEI)−gold nanocomposites, which activate macrophages and reprogram the tumor immunological microenvironment. 81 Additionally, Liang et al designed a core−shell gold nanocage coated with manganese dioxide, in which Au was designed as intrinsic inorganic photosensitizers mediating ROS generation. 37 4.1.1.2.…”
Section: The Biomaterials Science Of Tnbcmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, active targeting is achieved by delivering GNPs with tumour-specific targeted receptors/antigens for example GNP-conjugated EGFR monoclonal antibodies for binding with over-expressed receptors on tumour cells [ 59 ]. The polyethyleneimine (PEI)-coated cationic GNPs (AuPEI) shifted the immunological tumour microenvironment (TME) in the mouse breast MET-1 tumour model, in vivo, toward an M2 phenotype indicating immunosuppressive profile as determined by the increased PD-1 + (programmed death ligand)-positive lymphocytes [ 60 ]. The increase of PD-1 + CD8 + T cell population from 33.25 to 63.22% in presence of 2.5 µg/mlAuPEIs, in vivo, may increase the therapeutic efficacy of additional anti-PD-1 or anti-PD-L1 antibodies with better anticancer effect.…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%